Unrealistic Optimism and its Relationship Behavior with Smoking among Smokers: Comparative Study between Algerian Smokers Affected and not Affected with Lung Cancer - Machachou Guermia; Jabali Nourelddine (Journal of Educational and Psychological Studies, 2016)
This study aimed to find the relationship between the unrealistic optimism and smoking. To explore the relationship, two groups: smokers with cancer and smokers with no cancer were compared. The smoking behavior scale and the unrealistic behavior scale were administered to 130 persons of smokers without lung cancer and 112 smokers who had lung cancer. The SPSSl8 was used to obtain the meas, correlations, t-test and the analysis of variance. The study revealed a significant positive correlation between the unrealistic optimism and the number of daily smoked cigarettes for the smokers among non-lung cancer and a significant negative correlation between the unrealistic optimism and age and years of smoking among smokers without lung cancer. The study found a difference in unrealistic optimism among non-smokers with lung cancer due to educational level. Also, differences in unrealistic optimism between smokers infected and non-infected was found but in favor of non-infected.